Объяснение:
3
((х-3)(х-7))/12-((х-7)(х-1))/8+((х-1)(х-3))/24=1
(х^2-7х-3х+21)/12-(х^2-х-7х+7)/8+
+(х^2-3х-х+3)/24=(х^2-10х+21)/12-
-(х^2-8х+7)/8+(х^2-4х+3)/24=
=(2х^2-20х+42-(3х^2-24х+21)+
+х^2-4х+3)/24=(2х^2-20х+42-3х^2+24х-21+
+х^2-4х+3)/24=24/24=1
1=1 - верно
4
a/b=10 a=10b
(a-b)^2/ab=(10b-b)^2 / 10b×b=
=(9b)^2/10b^2=81b^2/10b^2=81/10=8,1
5
3+ a/(x+5) = 3x / (x+5)
3x+15+a=3x
a= - 15
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Объяснение:
3
((х-3)(х-7))/12-((х-7)(х-1))/8+((х-1)(х-3))/24=1
(х^2-7х-3х+21)/12-(х^2-х-7х+7)/8+
+(х^2-3х-х+3)/24=(х^2-10х+21)/12-
-(х^2-8х+7)/8+(х^2-4х+3)/24=
=(2х^2-20х+42-(3х^2-24х+21)+
+х^2-4х+3)/24=(2х^2-20х+42-3х^2+24х-21+
+х^2-4х+3)/24=24/24=1
1=1 - верно
4
a/b=10 a=10b
(a-b)^2/ab=(10b-b)^2 / 10b×b=
=(9b)^2/10b^2=81b^2/10b^2=81/10=8,1
5
3+ a/(x+5) = 3x / (x+5)
3x+15+a=3x
a= - 15